PTH-047 A Prospective Study on the Impact of a 'Bowel Cleansing Care Bundle' on Inpatient Colonoscopy Visualisation Scores: A London District Hospital Experience. (4th June 2013) - Fofaria, R K; Hamilton, N; Blackwell, V J; Sherman, D; Sharif, A W
Abstract : Introduction: It is recognised that a well prepared colon increases adenoma detection and removal rates 1 and the discovery of other significant pathology at endoscopy. Several factors can lead to a suboptimal outcome at inpatient colonoscopy but inadequate bowel preparation is a major contributor 2 . Potentially, this leads to repeat and/or alternative procedures and costly and prolonged hospital length of stays. 'Care Bundles' improve outcomes by decreasing the unwanted variation in clinical care and ensure the application of accepted clinical practices 3 . Consequently, we created a bowel cleansing bundle to address these issues and see whether it would lead to better visualisation scores. Methods: All inpatients requiring colonoscopy were recruited over two six-month periods at a London district hospital. A bowel cleansing bundle was devised formalising accepted clinical guidelines and it was implemented for all subsequent inpatient colonoscopies during the latter study phase. The bundle included sections on timings for the administration of bowel preparation agents, cessation of anti-motility agents, nutrition and hydration. Visualisation scores were noted from the endoscopists' reports (good, moderate and poor) and patients were followed up until discharge. Results: In total there were 93 eligible procedures. 53 patients in the pre-bundle population [56% Male, average age 69 years] and 40 patients in the post-bundle population [three exclusions, 57% male, average age 64 years] of which: 'good' visualisation scores = 45% vs 81%, 'moderate' = 21% vs 1% and 'poor' = 34% vs 16%. Implementation of the bundle led to significantly superior 'good' visualisation scores (p = < 0.001). P-value = 0.0008; two-tailed Fisher's exact test. Conclusion: Our study - the first looking at the effect of a bowel cleansing care bundle on inpatients - shows that its implementation conferred significantly better visualisation scores at colonoscopy with a dramatic reduction in poor visualisation. Disclosure of Interest: None Declared. References: Adler A, Wegscheider K, Lieberman D et al. Factors determining the quality of screening colonoscopy: a prospective study on adenoma detection rates, from 12 134 examinations. (BECOP-3). Gut. 2013 Feb; 62(2):236–41. Epub 2012 Mar 22. Canard JM, Arpurt JP, Boustiere C, et al. La coloscopie en France en 2004: résultat d'une enquête prospective nationale de la Société Française d'Endoscopie Digestive . Endoscopy 2006; 38: A1467. Resar R, Griffin FA, Haraden C, et al. Using Care Bundles to Improve Health Care Quality . IHI Innovation Series white paper. Cambridge, Massachusetts: Institute for Healthcare Improvement; 2012.